Coexistence of bla(NDM-1) and rmtC on a Transferrable Plasmid of a Novel ST192 Klebsiella aerogenes Clinical Isolate - Shen, Xiaofei (Infect Drug Resist, 2019)
INTRODUCTION: The occurrence and development of antibiotic resistance are mainly caused by the spread of large plasmids carrying multiple antibiotic resistance genes. Recently, the association between 16S rRNA methyltransferase genes and β-lactamase genes carried by the same plasmid is of concern. METHODS: The Klebsiella aerogenes 1564 was isolated from the catheter tip of a patient in a tertiary hospital, Shanghai, China. The presence of the bla(NDM-1) and rmtC genes were assessed by PCR. Complete sequence of plasmid p1564 was determined. The K. aerogenes 1564 was characterized by antimicrobial susceptibility testing, Carbapenemase phenotype confirmation testing, conjugation experiment, S1-PFGE and multilocus sequence typing (MLST). RESULTS: Herein, we found that a New Delhi Metallo-β-lactamase-1 gene (bla(NDM-1)) and a 16S rRNA methyltransferase gene (rmtC) coexisted on a transferrable plasmid of a carbapenem-resistant K. aerogenes clinical isolate. The K. aerogenes clinical isolate was found to belong to a novel sequence type 192 (ST192) determined by MLST. The sequencing results of the plasmid p1564 carrying bla(NDM-1) gene and rmtC gene showed that the size and guanine-cytosine content of the plasmid were 136, 902 bp and 51.8%, with 164 putative ORFs and two multidrug resistance gene islands. In addition to bla(NDM-1)and rmtC, the plasmid contained bleomycin resistance gene (ble(MBL)), CMY-6β-lactamase gene (bla(CMY-6)), quaternary ammonium compound resistance gene (sugE), truncated quaternary ammonium compound resistance gene (qacEΔ1), aminoglycoside resistance gene (aacA4) and sulfonamide resistance gene (sul1). By comparison, p1564 has high homology with pHS36-NDM from Salmonella enterica subsp. enterica serovar Stanley reported in China, with similar size and both belonging to plasmid incompatibility group A/C. CONCLUSION: The present study demonstrated for the first time the co-existence of rmtC and bla(NDM-1) in a novel ST192 K. aerogenes. The spread of plasmids harboring both bla(NDM-1) and rmtC may occur among Enterobacteriaceae in China.